ChemInform Abstract: Fe3O4 Nanoparticle‐Supported Copper(I): Magnetically Recoverable and Reusable Catalyst for the Synthesis of Quinazolinones and Bicyclic Pyrimidinones. Issue 12 (14th March 2013) - Yu, Lin; Wang, Min; Li, Pinhua; Wang, Lei
Abstract The developed catalyst exhibits excellent reactivity in the title synthesis and can be recycled over ten times in reactions without any obvious loss in its activity.